2006
DOI: 10.1159/000095593
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive-Impairment-Free Life Expectancy for Canadian Seniors

Abstract: Background/Aims: While cognitive impairment (CI) and dementia are among the most common morbid conditions in later life, life expectancies free from CI or dementia have been the object of much less investigation than life expectancy based on measures of physical functioning. Methods: We estimated sex-specific CI-free life expectancy in Canada for people aged 65 and older using data from a nationwide, multicenter Canadian study on the epidemiology of dementia. Results: The absolute number of years with CI remai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
22
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 50 publications
2
22
0
Order By: Relevance
“…Studies from the United Kingdom, the Netherlands, United States, and Canada, of which two were longitudinal, show that 5%–10% of TLE at age 65 years is spent with impairment and that this impairment burden is larger in women than men, but they do not investigate differences between education groups within the studies (913). …”
mentioning
confidence: 99%
“…Studies from the United Kingdom, the Netherlands, United States, and Canada, of which two were longitudinal, show that 5%–10% of TLE at age 65 years is spent with impairment and that this impairment burden is larger in women than men, but they do not investigate differences between education groups within the studies (913). …”
mentioning
confidence: 99%
“…First, institutionalized elderly subjects were not included our in study as well as in the studies from Japan [28] or the USA [33], while they were included in other previous studies from Canada, Europe, and Australia as well as in recent studies from the USA [34,35]. Some studies also covered only one or few cities/sites/areas/provinces and estimated the prevalence rates based on some health programmes, despite the fact that the samples were randomly recruited [21,23,24,25,27,29,68,69]. Most previous studies, such as in Europe and Australia, used a cross-sectional design, as did our present study, while the studies from Japan, Canada, the Netherlands, Brazil, the USA, and the UK used a longitudinal design.…”
Section: Discussionmentioning
confidence: 99%
“…Although the various forms of dementia are common morbid conditions and precursors of functional disabilities in later life, dementia-free LE (DemFLE) has been the object of less investigation than health expectancy based on other measures of physical functioning and health indicators [21]. According to the REVES bibliography database from 2013 [22], there were 1,516 scientific papers and/or reports related to LE with regard to different health dimensions, but few papers have been published in relation to DemFLE, and they have focused mainly on eight developed countries, namely Australia [23,24], Belgium [25], Canada [21,26], France [27], Japan [28], the Netherlands [29], the UK [30,31,32], and the USA [33,34,35], as well as on one developing country, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…in Canada and the United Kingdom) however these data are typically representative of populations in the 1990s. It is useful [3]. Using data from a field survey conducted in the over-70 population in Canberra and Queanbeyan in 1990-1991 (n=1,045) it was found that at 70 years of age, men were expected to live a further 11.95 years and women a further 15.12 years [6].…”
Section: Discussionmentioning
confidence: 99%
“…Healthy life expectancy is used to quantify the burden of disease and enables researchers to monitor the overall health of the population [2]. Cognitive impairment affects the functional status and quality of life not only of sufferers but also impacts their relatives and carers [2,3]. Dementia is Australia's third leading cause of death and there is no cure [4].…”
Section: Introductionmentioning
confidence: 99%